Occupational Safety of Pregnant Health Care Workers at the time of COVID-19 - Mangla, Mishu (Current Women's Health Reviews, 2023)
Coronavirus disease (COVID-19) is probably the biggest international crisis in Worldwar- 2. Health care workers are any country’s biggest asset at the time of coronavirus pandemic. A pregnant health care worker involved in patient care may face multiple risks for herself and her foetus. This article briefly discusses the problems faced by pregnant health care staff and works out possible solutions for the same. Workplace health protection for herself and her unborn fetus is the right of all pregnant health care workers and a uniform policy ensuring the same is the need of the hour.
Keywords: pregnancy